THE AUTOMATED HIGHWAY SYSTEM - DRIVERLESS TECHNOLOGY - Sharma, Piyush (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
An automated highway system (AHS) or Smart Road is a proposed intelligent transportationsystem technology designed to provide for driverless cars on specific rights-of-way. It is most often toutedas a means of traffic relief, as it would drastically reduce following distances and headway, thus allowing more cars to occupy a given stretch of road. It is a vehicle and road based system that can drive vehicleautomatically. This is done using sensors that serve as the vehicle’s eyes, determining lane position and thespeed and location of other vehicles. The concept of an Automated Highway has been around for a long time. But it has not been until recently that the technology has become available to build automated highways and vehicles. The AHS program is a broad international effort “to provide the basis for, andtransition to, the next major performance upgrade of the vehicle/highway system through the use of automated vehicle control technology”. The first vehicle in market with adaptive cruise control wasintroduced in 1997.